Formation of Gold Nanoparticle Self-Assembling Films in Various Polymer Matrices for SERS Substrates - Perova, Tatiana (My University, 2022)
Surface-enhanced Raman spectroscopy (SERS) is regarded as a versatile tool for studying the composition and structure of matter. This work has studied the preparation of a SERS substrate based on a self-assembling plasmonic nanoparticle film (SPF) in a polymer matrix. Several synthesis parameters for the SPF are investigated, including the size of the particles making up the film and the concentration and type of the self-assembling agent. The result of testing systems with different characteristics is discussed using a model substance (pseudoisocyanin iodide). These models can be useful in the study of biology and chemistry. Research results contain the optimal parameters for SPF synthesis, maximizing the SERS signal. The optimal procedure for SPF assembly is determined and used for the synthesis of composite SPFs within different polymer matrices. SPF in a polymer matrix is necessary for the routine use of the SERS substrate for various types of analytes, including solid samples or those sensitive to contamination. Polystyrene, polyvinyl alcohol (PVA), and polyethylene are investigated to obtain a polymer matrix for SPF, and various methods of incorporating SPF into a polymer matrix are being explored. It is found that films with the best signal enhancement and reproducibility were obtained in polystyrene. The minimum detectable concentration for the SERS substrate obtained is equal to 10−10 M. We prepared a SERS substrate with an analytical enhancement factor of 2.7 × 104, allowing an increase in the detection sensitivity of analyte solutions of five orders of magnitude.
PUBLISHED
Keywords: SERS; Self-assembling; Polymer matrix; Sensors; Nanoscience & Materials; Education